Student Development and Social Justice Critical Learning, Radical Healing, and Community Engagement - Hicks Peterson, Tessa (Springer International Publishing, 2018)
This book weaves together critical components of student development and community building for social justice to prepare students to engage effectively in community-campus partnerships for social change. The author combines diverse theoretical models such as critical pedagogy, asset-based community development, and healing justice with lessons from programs promoting indigenous knowledge, decolonization, and mindfulness. Most importantly, this book links theory to practice, offering service-learning classroom activities, course and community partnership criteria, learning outcomes, and assessment rubrics. It speaks to students, faculty, administrators, and community members who are interested in utilizing community engagement as a vehicle for the development of students and communities towards wellbeing and social justice.